PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASIONAL PADA KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Pada Pegawai BLUD RSUD Dr. Moewardi) - Ratna Tunjung Sari (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2018)
The purpose of this research was to examine the effect of leadership and organisational commitment on the performance of employees who mediated by the employee satisfaction of BLUD employee at Dr. Moewardi hospital.The sampling technique used is proportionate stratified non random sampling. Samples were are BLUD employee of RSUD Dr. Moewardi is 162 people. The validity test of using corrected item total correlation and reliability test using Cronbach’s Alpha. The hypothesis proposed using linear regression method by using SPSS 17 program.The result showed that leadership is positive and significant effect on employee satisfaction and employee performance, while organisational commitment is positive and significant effect on employee satisfaction and employee performance. Employee satisfaction mediates in partial effects of leadership and organisational commitment on employee performance. Keyword : Leadership, Organisational Commitment, Employee Satisfaction, Employee Perfomance